(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Most of the surface waters in India, including both rivers and lakes, are getting increasingly polluted due to onslaught of human activities of diverse nature. Though, several steps have been taken on a broader front including National River and Lakes Conservation Plans, but the quality of the water resources seems to be far from satisfactory.